Ocena stopnia uzależnienia społeczeństwa od smartfonów oraz zdrowotnych i psychospołecznych skutków ich używania = Assessment of the degree of dependence of society from smartphones, and health and psychosocial effects of their use - Sandra Ćwikła; Dominik Olejniczak (Kazimierz Wielki University, 2016)
Ćwikła Sandra, Olejniczak Dominik. Ocena stopnia uzależnienia społeczeństwa od smartfonów oraz zdrowotnych i psychospołecznych skutków ich używania = Assessment of the degree of dependence of society from smartphones, and health and psychosocial effects of their use. Journal of Education, Health and Sport. 2016;6(9):772-788. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159312 http://ojs.ukw.edu.pl/index.php/johs/article/view/3899       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016.       Ocena stopnia uzależnienia społeczeństwa od smartfonów oraz zdrowotnych i psychospołecznych skutków ich używania Assessment of the degree of dependence of society from smartphones, and health and psychosocial effects of their use   Sandra Ćwikła1, Dominik Olejniczak2   1 Absolwentka kierunku Zdrowie Publiczne Wydział Nauki o Zdrowiu Warszawski Uniwersytet Medyczny   2 Warszawski Uniwersytet Medyczny Zakład Zdrowia Publicznego ul. Banacha 1a, 02-097 Warszawa     Słowa kluczowe: smartfon, zachowania zdrowotne, uzależnienie, internet Key words: Smartphone, Health Behavior, Addiction, Internet     Streszczenie Wprowadzenie: Badania pokazują, że smartfon staje się nieodłącznym elementem życia współczesnego człowieka. Powodem, dla którego ludzie chętnie kupują i użytkują smartfony jest ich wielozadaniowość. Zadaniem aplikacji mobilnej jest niezależne od czasu i miejsca umożliwienie użytkownikom dostępu do informacji, komunikacji oraz rozrywki. Celem głównym badania własnego było określenie stopnia uzależnienia respondentów od smartfonów. Materiał i metoda: Badanie przeprowadzone zostało za pomocą metody sondażu diagnostycznego. Za narzędzie badawcze posłużył autorski kwestionariusz w wersji papierowej oraz elektronicznej. Kwestionariusz został wypełniony anonimowo przez 319 osób. Wyniki: Ponad 2/3 badanych deklaruje, że używa telefonu przez cały dzień bądź kilkanaście razy dziennie. Badanie własne pokazuje, że ponad połowa respondentów używa smartfony do celów służbowych (30%) lub służbowych I prywatnych (41%). Ponad połowa (58%) respondentów nie wyobraża sobie spędzenia tygodnia bez telefonu. Spośród wszystkich respondentów, aż 65% zaliczyłoby samych siebie do osób zależnych od smartfona. Wnioski: Praca biurowa jest często związana z używaniem telefonu komórkowego, co może być również powodem uzależnienia. Smartfony stały się nieodłącznym i niezastąpionym środkiem komunikacji. Powinno być realizowanych więcej kampanii informujących o zagrożeniach i negatywnych skutkach zbyt częstego użytkowania smartfonów.   Abstract Introduction: Studies show that smartphone becomes an integral part of modern man. Multi-tasking of smartphones is the reason why people are willing to purchase them and use it. The purpose of mobile application is to enable users access to information, communication and entertainment. The main objective of the study was to determine the degree of dependence from smartphones among respondents. Material and Methods: The survey was conducted using the diagnostic survey method. The original questionnaire was used as a research tool. The questionnaire was completed anonymously by 319 people. Results: More than 2/3 of respondents declare that they use mobile all day or several times a day. The study shows that more than half of the respondents use smartphones for business purposes (30%) or business and private (41%). More than half (58%) of the respondents can not imagine spending a week without a phone. Almost 65% of all respondents qualify themselves to the group of people dependent on the smartphone. Conclusions: Office work is often associated with the use of a mobile phone, which can also cause addiction. Smartphones have become an integral and indispensable means of communication. It should be carried out more campaigns informing about the dangers and negative effects of too frequent use of smartphones.